2016
DOI: 10.1093/cvr/cvw113
|View full text |Cite
|
Sign up to set email alerts
|

Induced NCX1 overexpression attenuates pressure overload-induced pathological cardiac remodelling

Abstract: Induced overexpression of NCX1 attenuated pressure overload-induced pathological cardiac remodelling. Thus, maintaining NCX1 activity may be a potential therapeutic strategy for preventing the progression of HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…The latter antibody was raised against a synthetic peptide corresponding to residues 102–114 of mouse Fam64a (CQSGTKWLMETQV). Samples were then labeled with fluorochrome-conjugated secondary antibodies (Thermo-Fisher) as described 25, 26 . When necessary, DAPI staining for DNA or phalloidin staining for F-actin filaments was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…The latter antibody was raised against a synthetic peptide corresponding to residues 102–114 of mouse Fam64a (CQSGTKWLMETQV). Samples were then labeled with fluorochrome-conjugated secondary antibodies (Thermo-Fisher) as described 25, 26 . When necessary, DAPI staining for DNA or phalloidin staining for F-actin filaments was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…To control expression level of NCX1 in cardiomyocytes, we used transgenic mice in which NCX1 expression was controlled by a cardiac-specific, DOX-dependent promoter, as previously described [1]. We crossed two lines of transgenic mice: one carrying the canine NCX1 gene under the control of the minimal cytomegalovirus promoter, and the other carrying a gene encoding the reverse tetracycline transactivator (rtTA) protein under the control of an α-myosin heavy chain promoter.…”
Section: Animalsmentioning
confidence: 99%
“…JP2 is a membrane-binding protein that physically connects the T-tubule membrane and SR membrane [5]. We and others have reported that T-tubule disorganization is associated with a significant decrease in JP2 expression [1,6,7]. In addition, JP2…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations